2012
DOI: 10.1186/1743-422x-9-100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Chikungunya virus from New Delhi reveal emergence of a new molecular signature in Indian isolates

Abstract: BackgroundChikungunya (CHIK) is currently endemic in South and Central India and exist as co-infections with dengue in Northern India. In 2010, New Delhi witnessed an outbreak of CHIK in the months October-December. This was the first incidence of a dominant CHIK outbreak in Delhi and prompted us to characterize the Delhi virus strains. We have also investigated the evolution of CHIK spread in India.FindingsClinical samples were subjected to RT-PCR to detect CHIK viral RNA. The PCR amplified products were sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…With reference to the Indian strains GQ996372/08 and HM159390/09, nucleotide divergence of 1% and 0.5% and protein divergence of up to 1% were detected. The mutations identified in the analyzed sequences were Lys211Glu, Met296Val, As-p284Glu and Val322Ala, all of which have previously been reported (22).…”
Section: Chikungunya Virusmentioning
confidence: 59%
“…With reference to the Indian strains GQ996372/08 and HM159390/09, nucleotide divergence of 1% and 0.5% and protein divergence of up to 1% were detected. The mutations identified in the analyzed sequences were Lys211Glu, Met296Val, As-p284Glu and Val322Ala, all of which have previously been reported (22).…”
Section: Chikungunya Virusmentioning
confidence: 59%
“…Amino acid sequence analyses showed that all 6 Bhutan isolates lack the E1 gene mutations, which led to the A226V E1 protein change found in the Réunion Island 06.49 strain and which are closely associated with a higher transmission rate (Figure 2) ( 10 ). In addition, the 2012 Bhutan strain still retained the E211 amino acid, which is also found in the India 2010 strain ( 11 ). …”
Section: The Studymentioning
confidence: 59%
“…In India, circulating CHIKV genotypes belong to the newly introduced ECSA lineage [2]. Two specific mutations, E1-K211E and E2-V264A, were detected in CHIKV strains isolated from New-Delhi revealing the emergence of a new signature in this clade [32]. Thus, other positions in the CHIKV genome exert strong epistatic effects on the E1-A226V substitution responsible for a significant increase in CHIKV transmission by Ae.…”
Section: Discussionmentioning
confidence: 99%